2006
DOI: 10.1080/10790268.2006.11753868
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Activation of Serotonin 1A Receptors Enhances Latent Respiratory Activity After Spinal Cord Injury

Abstract: Background/Objective: Hemisection of the cervical spinal cord results in paralysis of the ipsilateral hemidiaphragm. Removal of sensory feedback through cervical dorsal rhizotomy activates latent respiratory motor pathways and restores hemidiaphragm function. Because systemic administration of serotonin 1A receptor (5HT1A) agonists reversed the altered breathing patterns after spinal cord injury (SCI), we predicted that 5HT1A receptor activation after SCI (C2) would activate latent crossed motor pathways. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 35 publications
(66 reference statements)
3
30
0
Order By: Relevance
“…5-HT release associated with motor activity might play an indirect role in modulating motoneuron (MN) response as it has already shown by others using different preparations [8,10,16]. No serotonergic inhibition during basal condition (no movement) has been found and author data suggest that dorsal horn serotonin involvement in motor function may involve release of 5-HT and, its effect on multiple 5-HT receptor subtypes including 1B, 2A, 2C, 3, 4 [10].…”
Section: Serotonin Released In Dorsal Horn Might Be Specific Of Motormentioning
confidence: 80%
“…5-HT release associated with motor activity might play an indirect role in modulating motoneuron (MN) response as it has already shown by others using different preparations [8,10,16]. No serotonergic inhibition during basal condition (no movement) has been found and author data suggest that dorsal horn serotonin involvement in motor function may involve release of 5-HT and, its effect on multiple 5-HT receptor subtypes including 1B, 2A, 2C, 3, 4 [10].…”
Section: Serotonin Released In Dorsal Horn Might Be Specific Of Motormentioning
confidence: 80%
“…This reflex is a segmental spinal reflex that is most likely mediated through nonrespiratory interneurons located in the dorsal horn of the spinal cord (86,87). Application of 8-OH-DPAT, a 5HT-1A agonist, to the dorsal horn of the spinal cord increased phrenic motor output and activated the CPP (83). Thus, phrenic motor neurons were most likely disinhibited.…”
Section: Disinhibition Of Phrenic Motor Neuronsmentioning
confidence: 99%
“…Because cervical dorsal root rhizotomy increases serotonin innervation of phrenic motor neurons in the spinal cord (82), Fuller et al (47) suggested that the increased serotonin may act on 5HT-2A receptors located on phrenic motor neurons to increase their excitability and activate the ineffective crossed phrenic pathways. Another possibility is that the increased serotonin levels may also act in the dorsal horn on 5HT-1A receptors to decrease the excitability of dorsal horn sensory neurons (83). After SCI, dorsal horn sensory neurons become hyperexcitable, and studies have shown that an agonist of the 5HT-1A receptor, 8-hydroxy-DPAT-hydrobromide (8-OH-DPAT), can decrease the excitability of dorsal horn sensory neurons and attenuate mechanical allodynia and thermal hyperalgesia observed after SCI (84).…”
Section: Disinhibition Of Phrenic Motor Neuronsmentioning
confidence: 99%
“…To minimize possible interference of phrenic motor neurons directly or indirectly through local spinal 5-HT 1A R-dependent reflex in cervical spinal cord (Zimmer and Goshgarian 2006), we kept all spinal administrations of 5-HT 1A R agonist and antagonist at the lumbar level where 5-HT 1A R expression is reportedly the highest especially in the dorsal horn and rarely in the ventral horn (Marlier et al 1991;Thor et al 1993). Post-experimental Sky Blue injection (2 %, 20 ll at the same location of drug injection with 20 min diffusion time) showed that the Sky Blue staining of spinal cord was mainly within the lumbar level and no staining could be visually observed beyond lumbar level.…”
Section: Resultsmentioning
confidence: 99%